Parasitic Plants - Maria Gonzalez, Ana; Arnaldo Sato, Héctor (IntechOpen, 2022)
Over six chapters, this book deals with different aspects of parasitic plants, from generalities to specific case studies. A large part of the book deals with holoparasites that cause damage in agriculture, such as those of the genus Cuscuta. Their biology, forms of management, interaction with hosts as transmitting vectors, and even their phytochemistry and medicinal uses are analyzed. Cases of parasitic plants approached from the cultural relationship with humans are presented for an area of Africa, as well as a review of the biology of the American genus Lophophytum, a holoparasite that is not harmful to agriculture and is even in danger of conservation.